Reflection of Characterization in the Novel "Sarzamin-e- Jamila" - Danishyar, Ruhullah; Hagjo, Mohammad Nabi; Roshan, Mohammad (Journal of Social Sciences - Kabul University, 2025)
The purpose of this article is to examine the social and cultural behaviors of the characters in the novel Sarzamin-e-Jamila. The method of this reseache is narrative review and that is based on analysis and description, the research objective has been pursued and explored. The importance of the research is that it is a step for further research and it is necessary to examine and analyze it from this perspective. Sarzamin-e-Jamila, written by Siamak Heravi—one of Afghanistan’s contemporary authors—is a realist novel depicting the events of Afghan society during the 1380s (solar calendar). This research analyzes the characters according to gender, age, stability, and typicality, and explores the techniques of characterization through their names, physical appearances, and environments. From the perspective of character selection in fiction, the novel follows a classical approach and features predominantly classical types of characters. The characters are largely stereotypical and static, contributing to an unstable narrative flow.